How to read a film :movies, media, and beyond : art, technology, language, history, theory - Monaco, James (Oxford ; New York : Oxford University Press, 2009)
James Monaco discusses the elements necessary to understand how a film conveys its meaning, and, more importantly, how the audience can best discern all that a film is attempting to communicate.
Film as an art -- Technology : image and sound -- The language of film : signs and syntax -- The shape of film history -- Film theory : form and function -- Media : in the middle of things -- Multimedia : the digital revolution -- Film and media : a chronology -- Reading about film and media : a select library.
Includes bibliographical references (p. 678-691) and indexes.
Keywords: Motion pictures